Analysis of the survival of patients with breast cancer depending on age, molecular subtype of tumor and metabolic syndrome - Grybach, S.M.; Polishchuk, L.Z.; Chekhun, V.F. (Experimental Oncology, 2018)
Aim: To analyze the survival of patients with breast cancer (BC) depending on age, molecular subtype of the tumor and the presence of metabolic syndrome. Patients and Methods: We have analyzed the results of examination and treatment of 202 patients with BC of stages I–III. The patients were distributed by age into 2 groups. The group 1 included 86 elderly patients (from 65 to 84 years old), the group 2 — 116 younger patients (from 32 to 64 years). An overall 1-, 3- and 5-year survival rates of the treated patients were assessed. The significance of factors influencing the overall survival (OS) of patients with BC was determined using the methods of statistical analysis. Results: Molecular subtype of BC significantly affects survival rates: in a case of a luminal B subtype the 5-year OS was 71.6 vs 80% (p < 0.05) in groups 1 and 2, respectively while in a case of a basal-like subtype it was 60.2% and 71.6% (p < 0.05). The presence of metabolic syndrome significantly reduced the 5-year OS (up to 70.7% and 80.6%, p < 0.05 in groups 1 and 2, respectively). Conclusion: The OS is lower in elderly patients with BC compared with younger patients, especially in those who suffer from metabolic syndrome. Key Words: breast cancer, elderly age, metabolic syndrome, receptor status, 1-, 3-, 5-year overall survival.